Phytochemical prospecting and cytotoxicity assays of potential bioproducts to control parasites in Colossoma macropomum Cuvier (2022)
With the aim of determining economic and environmental alternatives that support fish farming in the State of Rondônia, a phytochemical prospection of genetic resources of the Rondônia flora was carried out. Subsequently, cytotoxicity assays against Artemia salina L. nauplii, thus observing those herbal medicines supposedly with greater potential to control parasites in fish, with emphasis on Tambaqui (C. macropomum). With regard to cytotoxicity assays, at least four herbal medicines showed a high potential, reaching values of 100% mortality of microcrustaceans, for the tested concentrations. They were extracted from Chenopodium ambrosioides (herb of Santa Maria or mastruz), Crotalaria cf. micans (maraca), Davilla sp. (fire vine, sp. 1) and Duranta sp. (during). The bioprospecting of RFG is also positioned as a conservation strategy.